A critical review on compressive behavior and empirical constitutive models of concrete. (14th March 2022) - Ouyang, Xue; Wu, Zemei; Shan, Bo; Chen, Qing; Shi, Caijun
Highlights: The recent developments in compressive behavior of concrete with low to high strength and corresponding established empirical and/or analytical constitutive models are reviewed. Factors affecting the compressive stress–strain relationships of plain concrete (PC), normal fiber reinforced concrete (NFRC) with compressive strength lower than 100 MPa, and ultra-high performance concrete (UHPC) are discussed. The compressive empirical constitutive equations in literatures are classified into three categories based on their formats. Ten commonly used models in standards and literatures are selected to simulate the stress–strain curves of PC, NFRC, and UHPC. The most effective ones for PC, NFRC, UHPC mixtures are identified. A general model for concrete with compressive strength ranging from 20 to 200 MPa is proposed based on the simulation results from the 10 selected models. Abstract: Knowing the development of compressive behavior of concrete with established appropriate constitutive model is fundamental for structure and component design and simulation, operations, such as removal of formwork, and prestressing or cracking control. This paper reviews the compressive behavior and empirical constitutive models of concrete with strength in the range from 20 to 200 MPa. Based on the characteristics of compressive behavior, concrete is first divided into three types, including plain concrete (PC), normal fiber reinforced concrete (NFRC) with a compressive strength lower than 100 MPa, and ultra-high performance concrete (UHPC). Characteristics of compressive stress–strain curves and their main influential factors, such as water-to-binder ratio, coarse aggregate type and content, fiber type and content, and curing condition, are then discussed. Three basic empirical constitutive models of concrete under compression, including proper rational fraction, improper rational fraction, and polynomial equations, for these concretes are classified and reviewed. Ten commonly used models in standards and literatures are selected to simulate the stress–strain curves of PC, NFRC, and UHPC. The most effective ones for PC, NFRC, UHPC mixtures are identified. Finally, a general equation for concrete with different strengths ranging from 20 to 200 MPa is proposed. This review aims to enhance the fundamental knowledge of compressive behavior of cement-based materials and help the selection of proper models given the concrete mixture proportion and basic performance.